Xijiao Dihuang Decoction Alleviates Ischemic Brain Injury in MCAO Rats by Regulating Inflammation, Neurogenesis, and Angiogenesis - Fei, Xiaojun (Evid Based Complement Alternat Med, 2018)
Ischemic stroke is an increasingly important public health problem, and no effective treatments are approved. Xijiao Dihuang Decoction (XDD), a famous herbal formula for treating hemorrhagic fever syndromes, has been shown to exert powerful neuroprotective property. The aim of this study was to identify the chemical constituents in XDD, observe the neuroprotective effect of XDD against acute ischemic stroke, and explore the specific mechanisms by which these effects were mediated. With UHPLC-Q/TOF-MS, 47 components in XDD were detected and 25 of them were identified. In rats subjected to MCAO, XDD ameliorated neurological deficit, histopathology changes, and infarction volume. In addition, levels of TNF-ɑ, IL-6, and IL-1β in XDD-treated group were significantly lower compared to the model group. Mechanistic studies showed that XDD inhibited MCAO-induced NF-κB activation, presenting as downregulating the expression of phospho-NF-κB p65 and preventing IκBɑ degradation. Besides, BDNF, GDNF, VEGF, bFGF, and CD34 levels were significantly increased by XDD, suggesting that the protective effects of XDD may also be associated with the promotion of neurogenesis and angiogenesis. In conclusion, these findings provided a novel regulatory pathway of the neuroprotective effect of XDD that helped rehabilitate patients with stroke.